Implementasi Pembelajaran Arah Mata Angin Melalui Metode Snowballing Throwing Pada Siswa Kelas 6 SD Negeri 014716 Simondong Kecamatan Sei Suka Kabupeten Batu Bara - Neliwati Neliwati; Rini Wahyuni Siregar; Wahida Raihan Nasution (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Learning according to Ahmad Faidi is a teaching activity between teachers and students. There is a lot of understanding among teachers that teaching is only an activity to lead students to understand teaching materials or subject matter, where the teacher just explains and gives assignments, while students listen and do the assignments from the teacher. This understanding is not wrong, but also not entirely correct. Social studies subjects in elementary schools are teaching programs that aim to develop the potential of students to be sensitive to social problems that occur in society. The scope of social studies subjects in elementary schools covers aspects of human (place and environment), time (sustainability and change), social and cultural systems, as well as economic behavior and welfare. The wind direction material is one of the social studies subject matter. With this material, students can identify and distinguish several cardinal directions. The cardinal points are guidelines for showing direction. With the cardinal points, we know the direction.Keywords: Learning, Cardinal Directions, Snowballing Throwing